Konsep dan Penerapan Model Kebijakan Corporate Environmental Responsibility di Indonesia - Syamsudin Isnaini; Amalia Diamantina (PROGRESIF: Jurnal Hukum, 2020)
The friction between economic interests and environmental interests has become a serious problem today. The friction between the two interests is evident in the activities of a company, therefore a company is given responsibility for the impact caused by its activities. This responsibility is â€œcorporate social and environmental responsibilityâ€. However, the term "Corporate Social Responsibility (CSR)" is often used in Indonesian society. The use of this term has a legal consequence, namely that the company's responsibility is only social responsibility, while environmental responsibility does not exist. Departing from these problems, this study will focus on discussing problems regarding the â€œCorporate Environmental Responsibility (CER)â€ policy model in Indonesia, particularly regarding the CER policy model, and the types of CER policies. This research is a normative juridical research with a statutory approach and a conceptual approach. The data used is secondary data in the form of laws and regulations and news about company and / or government programs in the field of environmental management. Based on the research results, it is known that the CER policy model clarifies and reinforces the regulation of corporate responsibility towards environmental aspects, CER policies can come from corporate initiatives or come from government initiatives.